Peer-editing patterns in the English one compositions of DLSU-Manila students - Cusipag, Maria N. (Philippine Journal of Linguistics, 2004)
The researcher examined the peer-editing patterns that De La Salle University-Manila first-year college students exhibited when editing the essays of their classmates. She attempted to answer the following questions: (1) What peer-editing patterns are used by college freshman students when editing the compositions of their classmates? (2) What ratings on form and content do these compositions obtain in the different peer-eating patterns used? (3) Are there significant differences among the peer-editing patterns used in terms of ratings on form and content? (4) Are there significant gains between drafts in both the ratings on form and content of compositions using different peer-editing patterns? Fray students belonging to one class analysed four model essays which were corrected using four editing patterns. They were instructed to choose one pattern which they were to use when editing the essays of their peers. Ten out of 40 students were allowed to choose one pattern. The last ten students who belonged to another class were not shown any of the four model essays to prevent them from being influenced by the patterns used by the other four groups. The respondents were asked to write an essay following a prompt. Their essays were edited by their peers using any of the patterns that they chose Those that were not shown any pattern edited the papers using their own strategy. Findings of the study proved that some form of editing resulted in considerable improvement in the student" argumentative essays. In addition, it was found that there was no significant difference in the mean gain scores among all the treatment groups which means that there is no one best pattern that results in significantly improved writing.